Effective Methylene Blue Removal from Aqueous Solutions using PVA/Chitosan Electrospun Nanofiber Modified with CeAlO3 Nanoparticles - Fatemeh Shahverdi; Aboulfazl Barati; Mansour Bayat (Journal of Water and Environmental Nanotechnology, 2022)
This research work aims to investigate the sorption characteristic of synthesized Poly (vinyl alcohol)/Chitosan nanofiber mats modified with aluminum-cerium spinel oxide (CeAlO3) nanoparticles for methylene blue (MB) removal from aqueous solutions. The sorption is carried out by a batch technique. The structural characterization of this nanocomposite was performed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analysis (XRD). Scanning electron microscopy (SEM) results showed uniform net and improved nanofibers with diameters ranging about 420 and 450 nm, respectively. The optimum conditions of MB removal onto modified PVA/CS nanofibers were found to be: pH 10, contact time 45 min, and 0.01 g of adsorbent in 400 ml in aqueous solution. Furthermore, the experimental adsorption data were in excellent agreement with the pseudo-second-order kinetics. The experimental results showed that there is a good correlation between the obtained data and the adsorption isotherm in the concentration range studied (400-600 mg/l). The results revealed that the maximum adsorption capacity of MB was 817.81 and 714.61 mg/g onto improved and net nanofibers, respectively.